The Influence of Promotion Costs and General Administrative to Cost of on PT. Jakarta International Hotels and Development.Tbk - Febryandhie Ananda; Safrul Rahmadhan (JURNAL PUNDI, 2020)
This research was conducted at PT. Jakarta International Hotels And Development.Tbk, which aims to determine the influence of promotion costs and the cost of administration against the price of staple inn. Using test tools Eviews 8, with secondary data from the years 2009-2018, quantitative research uses the data type of the time series. With the technique of multiple linear regression analysis, T test, and the test deteminasi (R2).The results of this study show that the Cost of Promotion significant positive effect on the financial performance of the Price of Staple Inn. So the hypothesis one in this study missed. It also happens in the variable Cost of Public Administration affect the financial performance of the Price of Staple Inn. So the hypothesis in this study positive significant. It can be seen from the results of t-Test showing the value prob is equal to 0.04 < alpha of 0.05. This means that the positive influence.